SgRVE6, a LHY-CCA1-Like Transcription Factor From Fine-Stem Stylo, Upregulates NB-LRR Gene Expression and Enhances Cold Tolerance in Tobacco - Chen, Shu; Huang, Huai-An; Chen, Jian-Hui; Fu, Cheng-Cheng; Zhan, Peng-Lin; Ke, Shan-Wen; Zhang, Xiang-Qian; Zhong, Tian-Xiu; Xie, Xin-Ming (Frontiers in Plant Science, 2020)
Stylosanthes species are economically important tropical and subtropical forage legumes which are generally vulnerable to chilling and frost. Fine-stem stylo (S. guianensis var. intermedia) has the most superior cold tolerance among all stylo species. A REVEILLE (RVE) gene, SgRVE6, was cloned from fine-stem stylo. Bioinformatic analysis suggests that SgRVE6 encodes a transcription factor of 292 amino acid residues, which belongs to the LATE ELONGATED HYPOCOTYL /CIRCADIAN CLOCK ASSOCIATED 1-LIKE (LCL) subgroup of RVE family and contains a SHAQKYF-class MYB domain and a LCL domain. SgRVE6 is universally expressed in root, stem and leaf tissues of fine-stem stylo and is rapidly up-regulated in all tested tissues under cold stress. Over-expressing SgRVE6 affects expression of 21 circadian clock genes, up-regulates expression of 6 nucleotide binding domain leucine-rich repeats (NB-LRR) encoding genes associated with tobacco cold tolerance, improves physiological responses to low temperature, and endows the transgenic tobaccos with higher tolerance to cold stress. This is the first time a study investigates the regulatory function of RVE6 in cold responses of plant species.